On Ground States of Discrete p(k)-Laplacian Systems in Generalized Orlicz Sequence Spaces - Juhong Kuang (Abstract and Applied Analysis)
Using the critical point theory, we establish sufficient conditions on the existence of ground states for discrete p(k)-Laplacian systems. Our results considerably generalize some existing ones.